Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24087671
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of Autophagy Induction under Cellular Stress and What Lies behind It, a Systems Biology Study

Abstract: One of the main inducers of autophagy-dependent self-cannibalism, called ULK1, is tightly regulated by the two sensor molecules of nutrient conditions and energy status, known as mTOR and AMPK kinases, respectively. Recently, we developed a freely available mathematical model to explore the oscillatory characteristic of the AMPK-mTOR-ULK1 regulatory triangle. Here, we introduce a systems biology analysis to explain in detail the dynamical features of the essential negative and double-negative feedback loops an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Cellular life-and-death decision is one of the most important tasks of a living organism to answer the drastic effects of various external and internal stimuli (such as endoplasmic reticulum stress, starvation, etc.). Recently, we have developed a simple mathematical model that was able to describe the important regulatory connections of the control network, claiming the importance of the double-negative feedback loops between the surviving and cell-death mechanisms [ 23 , 25 ]. We supposed that these feedback loops guaranteed the switch-like characteristic of the response corresponding to the level of cellular stress [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular life-and-death decision is one of the most important tasks of a living organism to answer the drastic effects of various external and internal stimuli (such as endoplasmic reticulum stress, starvation, etc.). Recently, we have developed a simple mathematical model that was able to describe the important regulatory connections of the control network, claiming the importance of the double-negative feedback loops between the surviving and cell-death mechanisms [ 23 , 25 ]. We supposed that these feedback loops guaranteed the switch-like characteristic of the response corresponding to the level of cellular stress [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have developed a simple mathematical model that was able to describe the important regulatory connections of the control network, claiming the importance of the double-negative feedback loops between the surviving and cell-death mechanisms [ 23 , 25 ]. We supposed that these feedback loops guaranteed the switch-like characteristic of the response corresponding to the level of cellular stress [ 23 , 25 ]. In the last couple of years, we also confirmed the important roles of various natural compounds (i.e., resveratrol, EGCG) in extending autophagy-dependent cell survival by postponing ER stress-induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hyperactivation of the ER stress response can also be dangerous for the cell (e.g., uncontrolled autophagy can cause cell death [153]), negative feedback loops in the system via eiF2a -> GADD34 −| eiF2α and ATF4 -> CHOP −| ATF4 are very important to prevent over-expression of the UPR members by the target proteins blocking their own activators [127]. Some experimental data have revealed that the negative feedback loop can cause the oscillatory characteristic of autophagy induction upon various stress events (such as rapamycin treatment or food deprivation), thus ensuring that the system can re-use the components generated by self-digestion, but not upon ER stress [154,155]. In a recent theoretical analysis, Erguler et al explore the dynamical characteristic of the ER stress response mechanism at various levels of stress, and they claim that the intermediate state of UPR, due to moderate level of ER stress, might generate sustained oscillation of the key components of the network [156].…”
Section: Discussionmentioning
confidence: 99%